2001
DOI: 10.1152/physiolgenomics.2001.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the response to thermal injury in human cells

Abstract: The genetic response of human cells to sublethal thermal injury was assessed by gene expression profiling, using macroarrays containing 588 complementary known genes. At 1, 4, 8, and 24 h following thermal injury, RNA was isolated, and a cDNA copy was generated incorporating (33)P and hybridized to Atlas arrays. About one-fifth of the genes on the membrane exhibited a significant elevation or depression in expression (>/=2-fold) by 4 h posttreatment. Genes for heat shock proteins (HSPs) were upregulated as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…An experiment reported in 1996 (94) used an array containing 1,000 genes to examine changes in gene expression in human T cells and demonstrated the feasibility of using this technology to identify new candidate heatresponsive genes. Another study involved exposing cultured human retinal pigment epithelial cells to sublethal heat shock (55°C for 3 s) (25). In a third, mice were immersed in 43°C water for 20 min and changes in gene expression in testes were examined (91).…”
Section: Changes In Expression Of Other Genes As a Results Of Heat Stressmentioning
confidence: 99%
“…An experiment reported in 1996 (94) used an array containing 1,000 genes to examine changes in gene expression in human T cells and demonstrated the feasibility of using this technology to identify new candidate heatresponsive genes. Another study involved exposing cultured human retinal pigment epithelial cells to sublethal heat shock (55°C for 3 s) (25). In a third, mice were immersed in 43°C water for 20 min and changes in gene expression in testes were examined (91).…”
Section: Changes In Expression Of Other Genes As a Results Of Heat Stressmentioning
confidence: 99%
“…Studies in which gene expression is analyzed by cDNA microarrays during the recovery phase after exposure to HS have demonstrated that HS modifies expression of many genes in addition to the classic HSPs, including those involved in regulation of transcription, growth, DNA repair, apoptosis, signaling, and cytoskeletal function (Dinh et al, 2001;Murray et al, 2004;Sonna et al, 2002a,b).…”
Section: Hsp and Heat Shock Factor-1mentioning
confidence: 99%
“…Recent DNA microarray and computational microarray analyzing technologies have provided a view of the expression (9,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). It is well known that cancer cells exposed to HT of more than 42.5˚C will undergo cell death, whereas exposure to MHT conditions, i.e., temperatures up to 42.5˚C, produces only slight or no cytotoxicity (26).…”
Section: Introductionmentioning
confidence: 99%